Co-activation: its association with weakness and specific neurological pathology - Wiles Charles M; Busse Monica E; van Deursen Robert WM (Journal of NeuroEngineering and Rehabilitation, 2006)
Abstract Background Net agonist muscle strength is in part determined by the degree of antagonist co-activation. The level of co-activation might vary in different neurological disorders causing weakness or might vary with agonist strength. Aim This study investigated whether antagonist co-activation changed a) with the degree of muscle weakness and b) with the nature of the neurological lesion causing weakness. Methods Measures of isometric quadriceps and hamstrings strength were obtained. Antagonist (hamstring) co-activation during knee extension was calculated as a ratio of hamstrings over quadriceps activity both during an isometric and during a functional sit to stand (STS) task (using kinematics) in groups of patients with extrapyramidal (n = 15), upper motor neuron (UMN) (n = 12), lower motor neuron (LMN) with (n = 18) or without (n = 12) sensory loss, primary muscle or neuromuscular junction disorder (n = 17) and in healthy matched controls (n = 32). Independent t-tests or Mann Witney U tests were used to compare between the groups. Correlations between variables were also investigated. Results In healthy subjects mean (SD) co-activation of hamstrings during isometric knee extension was 11.8 (6.2)% and during STS was 20.5 (12.9)%. In patients, co-activation ranged from 7 to 17% during isometric knee extension and 15 to 25% during STS. Only the extrapyramidal group had lower co-activation levels than healthy matched controls (p < 0.05). Agonist isometric muscle strength and co-activation correlated only in muscle disease (r = -0.6, p < 0.05) and during STS in UMN disorders (r = -0.7, p < 0.5). Conclusion It is concluded that antagonist co-activation does not systematically vary with the site of neurological pathology when compared to healthy matched controls or, in most patient groups, with strength. The lower co-activation levels found in the extrapyramidal group require confirmation and further investigation. Co-activation may be relevant to individuals with muscle weakness. Within patient serial studies in the presence of changing muscle strength may help to understand these relationships more clearly.